2017
DOI: 10.18632/oncotarget.17202
|View full text |Cite
|
Sign up to set email alerts
|

The role of autophagy in hepatocellular carcinoma: friend or foe

Abstract: Autophagy is an evolutionarily conserved lysosome-dependent catabolic process which degrades cell’s components in order to recycle substrates to exert optimally and adapt to tough circumstances. It is a critical cellular homeostatic mechanism with stress resistance, immunity, antiaging, and pro-tumor or anti-tumor effects. Among these, the role of autophagy in cancer is the most eye-catching that is not immutable but dynamic and highly complex. Basal autophagy acts as a tumor suppressor by maintaining genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
110
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(116 citation statements)
references
References 172 publications
0
110
0
Order By: Relevance
“…However, emerging evidence indicated that the self‐cannibalistic function may be associated with excessive cell death under certain conditions31, 32 Therefore, more and more scholars described the role of autophagy in various pathophysiological processes as a double‐edged sword 33, 34, 35, 36. From the previous study, the autophagy was proved to be a protective role for AKI37, 38 .…”
Section: Discussionmentioning
confidence: 99%
“…However, emerging evidence indicated that the self‐cannibalistic function may be associated with excessive cell death under certain conditions31, 32 Therefore, more and more scholars described the role of autophagy in various pathophysiological processes as a double‐edged sword 33, 34, 35, 36. From the previous study, the autophagy was proved to be a protective role for AKI37, 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin affects DNA excision repair cross complementary 1 (ERCC1) protein as well as Beclin‐1 and its autophagic moderator mammalian target of rapamycin (mTOR) (Bennukul et al, ) in a concentration‐dependent manner (Liu & Ryan, ). Beclin‐1 expression is negatively associated with HSC grade (Liu et al, ). MTOR inhibits ATG1 phosphorylation (Liu & Ryan, ).…”
Section: Introductionmentioning
confidence: 99%
“…AKT and ERK play crucial roles in cell proliferation, metastasis, angiogenesis, and drug response. The phosphorylated state of both AKT and ERK is indicative of the activity of tumor signaling (25,26). Moreover, a high expression of both proteins coincides with higher tumor cell viability and proliferation, and lower death in basic experiments, but a poorer prognosis in clinical practice (27).…”
Section: Discussionmentioning
confidence: 99%